Streptococcal Esophagitis in an Immunocompetent Patient: A Rare Sequelae - Lefika Bathobakae MD, MPH; Nader Mekheal MD; Derya Mücahit BS; Mina Fransawy Alkomos MD; Alisa Farokhian MD; Yana Cavanagh MD; Walid Baddoura MD (SAGE Publishing, 2024)
Infectious esophagitis (IE) is the leading cause of esophagitis, second only to gastroesophageal reflux disease. Infectious esophagitis is typically observed in immunocompromised individuals due to neutropenia, HIV/AIDS, solid organ malignancies, cancer-directed therapy, or chronic steroid use. The most common causes of IE are herpes simplex virus (HSV), cytomegalovirus (CMV), and Candida albicans . Acute bacterial esophagitis is exceedingly rare, particularly in immunocompetent patients. Herein, we describe a unique case of acute streptococcal esophagitis in a male patient with no pertinent medical history. The patient's substernal chest pain and odynophagia resolved after antibiotic treatment.